Calculating regional stresses for northern Canterbury: the effect of the 2010 Darfield earthquake. Issue 1 (2nd January 2016) - Ellis, S; Williams, C; Ristau, J; Reyners, M; Eberhart-Phillips, D; Wallace, LM
ABSTRACT: We model regional stresses before and after the M w 7.1 Darfield earthquake of September 2010 in Canterbury, New Zealand including crustal structure derived from seismic tomography. Models show that the Banks Peninsula volcanic assemblage acts as a strong, rigid block that pinches out ductile layers in the mid-crust but has little effect on shallower principal stress orientations. Static stress changes from the Darfield earthquake are everywhere <25 MPa except within 5 km of the fault. When added to regional stresses, these create only small rotations of <5° in the orientation of maximum horizontal stress S Hmax, even near the fault. Predicted stress rotations do not correlate strongly with those inferred from aftershock focal mechanisms. The perturbations caused by earthquake stresses are not significant enough to explain either the magnitude or the sense of S Hmax rotations near the fault at seismogenic depths.